Bioenhancing effects of naringin on atrovastatin - Sama Venkatesh; Balaraju Pagilla; Rajeswari Chiluka; Ravi Alvala; Ravi Kumar Pola; Ramesh Mullangi (International Association of Physical Chemists (IAPC), 2019)
Naringin (CAS no: 10236-47-2) is a flavonone glycoside obtained from Citrus paradisi (grapefruit), a natural bioenhancer and reported to enhance the bioavailability of drugs by inhibiting cytochrome P450 and P-glycoprotein (P-gp). The aim of the present study was to investigate the effect of naringin on antihyperlipidemic properties of atorvastatin (AST) in tyloxapol induced hyperlipidemic rats and the effects were supported with measurement of plasma concentrations of AST by HPLC method. Animals received AST along with naringin (15 and 30 mg/kg) shown higher percent reduction in both cholesterol and triglycerides levels, when compared to animals received AST alone at dose of 25 and 50 mg/kg and it was found that the higher percent reduction in cholesterol and triglycerides was proportional to increase in plasma concentration of AST. From the results it is evident that the co-administration of naringin along with AST increased the plasma concentration of AST. The findings of the present study confirmed that naringin could be used as bioenhancer. The co-administration of AST and the diet with naringin (grapefruit) to the patients may potentiate the therapeutic efficacy of AST.